A prospective study on maximal oxygen uptake and cardiovascular functions in 12-year-old endurance athletes and their non-endurance-trained peers - Grendstad, H.; Ådnegard Skarstad, S.; Edvardsen, T.; Hallén, J. (Scandinavian Journal of Medicine & Science in Sports, 2025)
The maximal oxygen uptake (VO2max) is typically higher in endurance-trained adolescents than in non-endurance-trained peers. However, the specific mechanisms contributing to this remain unclear, as well as the impact of training during this developmental stage. This study aims to compare VO2max and cardiovascular functions between 12-year-old endurance athletes and non-endurance-trained over a 14-month period. Anthropometrics, VO2max, hemoglobin mass (Hbmass), blood volume (BV), and left-ventricular morphology were assessed four times over the 14 months in a group of young cross-country skiers (END, n = 42, age: 12.4 ± 0.5, girls: n = 27) and a group of controls (CON, n = 26, age: 12.3 ± 0.3, girls: n = 15). Throughout the 14-month follow-up, END did more weekly training than CON (7.0 ± 2.3 vs. 2.5 ± 2.4 h, p < 0.001), with only END conducting endurance training. END had ~18% higher VO2max relative to fat-free mass (FFM) than CON (p < 0.001). Stroke volume (SV) and left ventricular end-diastolic volume (LV EDV) relative to FFM were also higher for END than CON (p < 0.001 and 0.004), while no significant differences were found for Hbmass and BV. No significant interaction was seen for group and time for V?O2max (p = 0.352-0.767) or any cardiovascular parameters (p = 0.131-0.956) in absolute measures or relative to FFM. In conclusion, the END group exhibited higher VO2max, LV EDV, and SV compared to the CON group, with no significant difference in BV and Hbmass. Despite substantial differences in training volume, the progression of these variables over the 14-month period was similar in both groups.